2017
DOI: 10.1155/2017/5671584
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological Production Process and Life Cycle Assessment of Graphene

Abstract: The aim of this study is to compare the graphene produced using a biotechnological method (Escherichia coli) with the graphene produced by Hummers’ method (a chemical method) and to study the effect on the energy consumption and environment. The results indicated that the chemical reduction process has higher energy consumption, approximately 1642 Wh, than the energy consumption of the biotechnological reduction process, which is 5 Wh. The potential of global warming (GWP 100) improved by 71% using the biotech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Few LCA studies are available on carbon nanomaterials, and most of these focus on carbon nanotubes production like in Griffiths et al (2013) or Trompeta et al (2016) or are focused on a specific application such as electromagnetic shielding for satellites (Pourzahedi et al, 2017). Fewer studies have evaluated graphene, considering a range of graphene production routes, including chemical synthesis (Arvidsson et al, 2014), epitaxial growth (Arvidsson and Molander, 2017), a range of chemical, electrochemical and chemical vapour deposition routes (Cossutta et al, 2017), and a biotechnological production route (Khanam et al, 2017). Only a small number of LCA studies have considered graphene uses, including polymer fillers (Long et al, 2018), transparent electrodes (Arvidsson et al, 2016), corrosion inhibition (Upadhyayula et al, 2017), and conductive plating (Guarino et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Few LCA studies are available on carbon nanomaterials, and most of these focus on carbon nanotubes production like in Griffiths et al (2013) or Trompeta et al (2016) or are focused on a specific application such as electromagnetic shielding for satellites (Pourzahedi et al, 2017). Fewer studies have evaluated graphene, considering a range of graphene production routes, including chemical synthesis (Arvidsson et al, 2014), epitaxial growth (Arvidsson and Molander, 2017), a range of chemical, electrochemical and chemical vapour deposition routes (Cossutta et al, 2017), and a biotechnological production route (Khanam et al, 2017). Only a small number of LCA studies have considered graphene uses, including polymer fillers (Long et al, 2018), transparent electrodes (Arvidsson et al, 2016), corrosion inhibition (Upadhyayula et al, 2017), and conductive plating (Guarino et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…All studies included in this section reported direct contributions from the production of GRMs, however, the system boundaries varied from 'cradle to gate' , [188,[195][196][197][198][199][200][201] 'cradle to installation' [202] and 'cradle to grave' [189]. The functional unit varied across these studies, with the large majority defined in terms of mass, e.g.…”
Section: Environmental Impacts Of Graphene-related Materials Producti...mentioning
confidence: 99%
“…The LCA study of graphene grown by epitaxial method [91] revealed that thinner SiC wafer and use of renewable energy sources has to be implemented in order to achieve the environmental impact. Kahnam et al [92] compared the LCA of graphene grown by biotechnological process and chemical process and found that in chemical process more energy is consumed (1642 Wh), than in the biotechnological process (5 Wh). All together it can be stated that in each production process of graphene there is a step (reduction step in chemical reduction of graphite oxide, heating step in thermal exfoliation, hydrocarbon gas feedstock for CVD, production of the silicon carbide wafer for epitaxial growth) is mainly responsible for huge environmental impact [93].…”
Section: Life Cycle Assessment (Lca)mentioning
confidence: 99%